(untitled) (Current Problems in Rail Vehicles, 2021)
The paper describes the unfortunate consequences of a poorly made press wheel-axle joint, which lead to cracks in the area of the axle seat and, in rare cases, to total fracture of the axles with all the severe consequences. In the practical implementation of a press connection, in accordance with normative regulations, the wheel is pressed "cold" on the axle by the pressing force, which is recorded during the pressing and is actually the only control parameter of the resulting press connection. However, this parameter is completely insufficient from the point of view of the quality of the pressed joint, or it does not have a sufficient telling level about the strength of the pressed joint. The paper contains a description of a more consistent way of checking the made press connection, which would guarantee that only wheelsets with high-quality pressed wheels on the axle would get into operation.